Answer:
0 = 0
The equation is an identity, all real numbers are solutions.
Explanation:
First we simplify:
4[24 + -3(7x + 6)] + -6(4 + -14x) = 0
Then we need to reorder the terms:
=> 4[24 + -3(6 + 7x)] + -6(4 + -14x) = 0
=> 4[24 + (6 * -3 + 7x * -3)] + -6(4 + -14x) = 0
=> 4[24 + (-18 + -21x)] + -6(4 + -14x) = 0
We the have to combine like terms:
24 + -18 = 6
=> 4[6 + -21x] + -6(4 + -14x) = 0
=> [6 * 4 + -21x * 4] + -6(4 + -14x) = 0
=> [24 + -84x] + -6(4 + -14x) = 0
=> 24 + -84x + (4 * -6 + -14x * -6) = 0
=> 24 + -84x + (-24 + 84x) = 0
Reorder the terms again:
24 + -24 + -84x + 84x = 0
Combine like terms again:
24 + -24 = 0
=> 0 + -84x + 84x = 0
=> -84x + 84x = 0
Then once again, combine like terms:
-84x + 84x = 0
=> 0 = 0